1993
DOI: 10.1084/jem.177.6.1623
|View full text |Cite
|
Sign up to set email alerts
|

Clonal V alpha 12.1+ T cell expansions in the peripheral blood of rheumatoid arthritis patients.

Abstract: Rheumatoid arthritis (RA) represents a heterogenous disease characterized by chronic polyarthritis. Most patients with adult RA inherit HLA-DR4 or -DR1 major histocompatibility complex (MHC) genes. While the molecular basis for this genetic predisposition is unknown, the major function of these MHC-encoded molecules is to present peptides to T lymphocytes. It is hypothesized that an endogenous or environmental antigen initiates a MHC-restricted immune response mediated by T lymphocytes, which is followed by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
50
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(56 citation statements)
references
References 61 publications
(58 reference statements)
6
50
0
Order By: Relevance
“…Clonal abnormalities of circulating T cells have been described in RA patients. Clonal expansions have been found predominantly in CD8+ T cells studies have shown that clonal expansion can be found in at least 10% of the RA population studied (34). We have also observed clonal expansion of CD4+ T cells in patients with RA (26).…”
Section: Discussionsupporting
confidence: 71%
“…Clonal abnormalities of circulating T cells have been described in RA patients. Clonal expansions have been found predominantly in CD8+ T cells studies have shown that clonal expansion can be found in at least 10% of the RA population studied (34). We have also observed clonal expansion of CD4+ T cells in patients with RA (26).…”
Section: Discussionsupporting
confidence: 71%
“…In addition to the TCR V, MAb, we also studied TCR V,12 expression (data not shown) and did not observe an increased frequency of TCR V,12+ expansions (2 of 25 RA patients versus 2 of 24 controls) as previously reported (37). There are a number of possible explanations that may account for the differences between our and other (34-37) studies.…”
Section: Discussionsupporting
confidence: 50%
“…Second, different antigens may generate the CD8high+(CD57+) subset. Third, TCR usage may be biased by HLA haplotypes; for example, an association between increased frequency of TCR V,12 and HLA-DQw2 has been described (37). We found no significant associations between RA patients with TCR V,5 and V,13 expansions and their MHC I haplotypes, though the small numbers and the nature of the anti-TCR V,5 and V,13 MAb (discussed above) preclude any conclusions concerning MHC restriction.…”
Section: Discussionmentioning
confidence: 47%
“…Of note, DerSimonian et a1 recently found that -15% of RA patients without neutropenia or lymphocytosis demonstrated clonal expansions of CD8+ T cells bearing the VJ2.1 T cell receptor (15). However, among those 8 patients, only 3 were DR4+, although 7 of the 8 were DQ2+ (15). No such increase in DQ2 was seen in our patients with LGL leukemia plus RA.…”
Section: Discussionmentioning
confidence: 41%
“…This pattern is not consistent with proliferation of LGL due to a superantigen, which should induce a restricted pattern of T cell receptor V, usage. Of note, DerSimonian et a1 recently found that -15% of RA patients without neutropenia or lymphocytosis demonstrated clonal expansions of CD8+ T cells bearing the VJ2.1 T cell receptor (15). However, among those 8 patients, only 3 were DR4+, although 7 of the 8 were DQ2+ (15).…”
Section: Discussionmentioning
confidence: 97%